Pengaruh Pelatihan dan Pengembangan Produktivitas Terhadap Hasil Kinerja dan Karir Karyawan - Youngky Odies S; Moch Haifan F; M Farit Rusdiawan; Adam Hadiansyah; Ribangun Bamban Jakaria (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
Employee training and development is an activity that aims to improve employee competence, knowledge and attitudes in achieving achievement. This training is provided to both new employees and existing employees who still need training and retraining. In practice, training is a short-term development process that uses a structured and organized operating system, with the main aim of improving employee performance and opening up career opportunities. Employees need to have sufficient skills and knowledge, and one way to meet these needs is through training programs designed to improve the quality of human resources. In this way, employees can achieve their desires and ultimately get the expected results.